ANALISIS FAKTOR-FAKTOR KEKALAHAN TIM NASIONAL FUTSAL INDONESIA DI AFF CHAMPIONSHIP 2018 STUDI KASUS BERDASARKAN STATISTIK PERTANDINGAN - ANGGIA SWASTIKA, WIDI; WIDODO, ACHMAD (Jurnal Kesehatan Olahraga, 2019)
The role of statistics in futsal matches is to give a picture of a match to players, coaches, or spectators. Statistics in futsal matches contain numbers that describe events in a match. Match statistics also have an important role for the coach, namely for material evaluation and analyzing the strengths or weaknesses of opponents to be faced. The purpose of the study was to analyze the factors of Indonesias defeat in theAFF championship 2018case study based on match statistics. This research uses descriptive by using percentage formula and mean. The process of retrieving data uses match statistics.The results showed that: 1) in the Indonesian group phase match against Malaysia, Indonesia excelled in the statistical component of Passing Success which was equal to 84.11% (233 passes successfully entered from 277 total passing), passing failedwhich was 15.88%(44 passings failedof 277 total passes), Shot on Target is equal to 40% (20 Shot on target of 50 total shots), Shot off target is as much as 60% (30 Shot off targets of 50 total shots). Whereas Malaysia in thecomponent ofstatistics Passing Successfulis equal to 82.96% (224 Passing successfully entered from 270 Total Passing), Passing failed which is equal to 17.03%(46 Passing failed from 270 Total Passing), Shot on Target that is equal to 44.11% (15 Shot on target from 34 total shots), Shot off target that is as much as 55.88% (19 Shot off targets from 34 total shots). 2) in the Indonesian semi-final match against Thailand, Thailand excelled in thestatistical component Passing Successfulwhich was 92.15% (364 passes successfully entered from 395 total passing), passing failedwhich was 7.84%(31 passes failedfrom 395 total passes), Shot on Target which is equal 196 to 56.89% (33 Shot on targets from 58 total shots), Shot off the target as many as 43.1% (25 Shot off targets from 58 total shots). Indonesia in thecomponent ofstatistics Passing Successfulis 83.05% (250 Passings have been successfully entered from 301 Total Passing), Passing failed which is 16.94%(51 Passings failed from 301 Total Passing), Shot on Target which is equal to 50% (18 Shot on target of 36 total shots), Shot off target that is as much as 50% (18 Shot off targets of 36 total shots). Keywords: futsal, statistics